An Analysis of User Satisfaction Toward the Maxim Application in Medan City using the E-Servqual Model - Agil, Rezkyta; Octaviandy, Pieter; Tarigan, Feriani Astuti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The development of information technology has facilitated various activities, including online transportation services. Maxim, as one of the digital transportation service providers, has received numerous user complaints, particularly regarding its navigation features, interface design, and electronic payment system. This study aims to analyze user satisfaction with the Maxim application in Medan City using the E-Servqual method, which includes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research used a quantitative approach by distributing online questionnaires to 104 respondents. The results showed that all dimensions had negative GAP values, with tangibles being the most dominant factor affecting user satisfaction. As a solution, a real-time dashboard prototype was designed to help developers monitor feature evaluations directly. This research is expected to serve as a reference for improving the quality of Maxim’s services in the future.